Spinal cord injury induces transient activation of hepatic stellate cells in rat liver - Inmaculada Fernandez-Canadas; Alejandro Badajoz; Jesús Jimenez-Gonzalez; Martin Wirenfeldt; Beatriz Paniagua-Torija; Clara Bravo-Jimenez; Mar Del Cerro; Angel Arevalo-Martin; Daniel Garcia-Ovejero (Scientific Reports)
Abstract Spinal cord injury (SCI) causes abnormal liver function, the development of metabolic dysfunction-associated steatotic liver disease features and metabolic impairment in patients. Experimental models also demonstrate acute and chronic changes in the liver that may, in turn, affect SCI recovery. These changes have collectively been proposed to contribute to the development of a SCI-induced metabolic dysfunction-associated steatohepatitis (MASH). However, none of the existent studies have focused on hepatic stellate cells (HSCs), liver resident cells that are the primary drivers of collagen deposition and fibrosis following sustained liver damage. Here, we describe the transient activation of HSCs after a thoracic contusion in rats, considered a clinically relevant model of experimental SCI. We studied HSC during the time course of SCI, from 1 to 45 days post injury. We found a transient activation of HSCs after SCI, beginning with the acute downregulation of Glial Fibrillar Acidic Protein 1dpi. This is followed by a morphological and phenotypical transformation into alpha-smooth muscle actin (ACTA2/SMA) immunoreactive myofibroblast-like cells, peaking at 14 days post-injury and returning to control-like levels at later timepoints (45 days post-injury). These changes are not accompanied by fibrosis development but collagen deposition in peri-portal areas is observed at 45 days.